Effect of Emotional Intelligence on Student Learning Achievement - Hadiwijaya, Hendra (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
The Effect of Emotional Intelligence Against Student Achievement aims to determine the effect of emotional intelligence which consists of self awareness, self management, Motivation, social awareness, relationship management partially and simultaneously on learning achievement. Respondents are students of SMP Negeri 4 Lalan Bumi Agung  Vilage Musi Banyuasin Regency to be 135 people. Methods of data analysis using regression analysis techniques. Partial assay results (t-test) showed emotional intelligence consists of Self awareness, self management, Motivation, social awareness, relationship management positive and significant effect on learning achievement. Simultaneous Test Results (Test-F) emotional intelligence consists of Self awareness, self management, motivation, social awareness, relationship management and significant positive effect on learning achievement. Social awareness is more dominant influence on learning achievement.